The Effectiveness of Utilizing Facebook Media on the Home Notification Page to Improve Poetry Writing Ability at Class X SMA NURUL IMAN - Pratiwi, Fadhillah; Harahap, Rosmawati (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2023)
The research was carried out which aims to describe the use, application, and use of Facebook media on the notification page of the homepage in writing poetry by students of class X SMA Nurul Iman. This study used a quantitative descriptive method with a population of 180 people and a set sample of 27 people. The total selection was 15% of the total population. The highest score obtained was 90 while the lowest score was 75. Based on the results of data analysis, the average score of class X SMA Nurul Iman students was 81.85 (85%) which was categorized as "good". The ability to use the Facebook home page by the tenth-grade students of SMA Nurul Iman based on the poetry writing test on the Facebook notification homepage was 69.00 which was included in the "sufficient" category. This was evidenced by the results of the poetry writing test with an average score of 81.85 (good). The average score for writing poetry on the Facebook notification homepage for class X students of SMA Nurul Iman for the academic year 2021-2022 was 81.85 which qualified into the category B (Good).